“Be Pagan Once Again”: Folk Music, Heritage, and Socio-sacred Networks in Contemporary American Paganism - Chase, Christopher (Pomegranate, 2007)
Religious music serves to co-create and carry strategies of theology, authenticity, and behavior. This article examines the history of folk music and folk ideology in creating and maintaining such strategies. I examine several prominent examples of American folk music and Pagan music, articulating their shared historical and theological relationships. Focusing on nationalism, feminism, and populism, I also argue that an ideology of the common ritual year is a prominent shared theme between American folk music and contemporary Paganism. While underscoring the need for greater attention to this area, the article concludes that the legitimization processes at work are similar to other American heritage musics and aspects of American cultural politics.